2013
DOI: 10.1186/1471-2350-14-41
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imbalances in patients with a clinical presentation in the spectrum of Cornelia de Lange syndrome

Abstract: BackgroundCornelia de Lange syndrome (CdLS) is a rare autosomal-dominant disorder characterised by facial dysmorphism, growth and psychomotor developmental delay and skeletal defects. To date, causative mutations in the NIPBL (cohesin regulator) and SMC1A (cohesin structural subunit) genes account for > 50% and 6% of cases, respectively.MethodsWe recruited 50 patients with a CdLS clinical diagnosis or with features that overlap with CdLS, who were negative for mutations at NIPBL and SMC1A at molecular screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…GHRH haploinsufficiency may lead to isolated growth hormone deficiency (GHD) and justify the marked prenatal and postnatal growth retardation found in our patient and in about half of the published cases [Callier et al, 2006;Iqbal and Al-Owain, 2007;Hiraki et al, 2011;Gervasini et al, 2013;Posmyk et al, 2014;Jedraszak et al, 2015]. This hypothesis seems to be supported by the reduced IGF1 levels in our patient.…”
Section: )supporting
confidence: 74%
See 2 more Smart Citations
“…GHRH haploinsufficiency may lead to isolated growth hormone deficiency (GHD) and justify the marked prenatal and postnatal growth retardation found in our patient and in about half of the published cases [Callier et al, 2006;Iqbal and Al-Owain, 2007;Hiraki et al, 2011;Gervasini et al, 2013;Posmyk et al, 2014;Jedraszak et al, 2015]. This hypothesis seems to be supported by the reduced IGF1 levels in our patient.…”
Section: )supporting
confidence: 74%
“…Mutations and deletions of SAMHD1 have been associated with systemic lupus erythematosus, and recently homozygous mutations in SAMHD1 were found in 8.3% of Jedraszak et al, 2015Callier et al, 2006Iqbal et al, 2007Hiraki et al, 2011Gervasini et al, 2013Posmyk et al, 2014 Total reported patients Our case (DECIPHER…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 This is a clinically heterogeneous developmental disorder characterized by malformations affecting multiple systems, including dysmorphic facial features, distal limb defects, cleft palate growth retardation and developmental delay. [35][36][37][38][39][40][41] Mutations in HUWE1 cause XLID with moderate-to-severe ID often coupled with disturbances to speech development. 20,42,43 Of the ID genes in this cluster, HUWE1 is the only one known to be dosage-sensitive, with twofold overexpression in males leading to mild-to-profound cognitive impairment in syndromic XLID, Turner type.…”
Section: Xp112 Microduplications C Moey Et Almentioning
confidence: 99%
“…Among these, 17 scientific articles met the criteria for inclusion and were selected for this study (D'Angelo et al, 2006;Krepischi-Santos et al, 2006;Kang et al, 2007;Robinson et al, 2008;Bursztejn et al, 2009;El-Hattab et al, 2010;Gajecka et al, 2010;Rosenfeld et al, 2010;Haimi et al, 2011;Mikhail et al, 2011;Nicoulaz et al, 2011;Giannikou et al, 2012;Gervasini et al, 2013;Shiba et al, 2013;Zhu et al, 2013;Shimada et al, 2014;Stagi et al, 2014). Among these, 12 were case reports and five reported series of cases.…”
Section: Resultsmentioning
confidence: 99%